2019
DOI: 10.4103/ams.ams_17_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of vital surgical parameters, after administration of midazolam and dexmedetomidine for conscious sedation in minor oral surgery

Abstract: Aim:The aim of this study is to compare the efficacy between midazolam and dexmedetomidine in relation to vital parameters, sedation score, pain score, cognitive judgment, and postoperative amnesia to the event in conscious sedation for minor oral surgical procedure.Materials and Methods:A sample size of 30 patients were selected in each group: Group M (midazolam) and Group D (dexmedetomidine).Results:The mean heart rate (HR) and systolic and diastolic blood pressure measurements were significantly higher in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Opioids were associated with a statistically significant mean reduction in respiratory rate of 18% (95% CI 12–24%, p < 0.0001, 24 arms), 15 , 20 , 21 , 33 , 35 , 39 , 46 , 51 , 55 , 56 , 61 , 62 , 65 whereas inhaled sevoflurane was associated with an increase in respiratory rate of 83% (95% CI 49–118%, p < 0.0001, 1 arm). 28 Mean percent changes in respiratory rate were close to zero and not statistically significant with exposure to benzodiazepines (2% decrease, 95% CI 9% decrease-6% increase, 16 arms), 19 , 26 , 27 , 29 , 37 , 42 , 43 , 47 , 50 , 59 , 63 , 64 other hypnotic agents (2% decrease, 95% CI 9% decrease-5% increase, 17 arms), 17 , 23 , 26 , 29 , 30 , 31 , 32 , 34 , 36 , 41 , 44 , 48 , 49 , 59 and propofol (4% increase, 6% decrease-14% increase, 9 arms) 16 , 17 , 30 , 41 , 52 , 54 , 60 , 61 , 63 ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 87%
“…Opioids were associated with a statistically significant mean reduction in respiratory rate of 18% (95% CI 12–24%, p < 0.0001, 24 arms), 15 , 20 , 21 , 33 , 35 , 39 , 46 , 51 , 55 , 56 , 61 , 62 , 65 whereas inhaled sevoflurane was associated with an increase in respiratory rate of 83% (95% CI 49–118%, p < 0.0001, 1 arm). 28 Mean percent changes in respiratory rate were close to zero and not statistically significant with exposure to benzodiazepines (2% decrease, 95% CI 9% decrease-6% increase, 16 arms), 19 , 26 , 27 , 29 , 37 , 42 , 43 , 47 , 50 , 59 , 63 , 64 other hypnotic agents (2% decrease, 95% CI 9% decrease-5% increase, 17 arms), 17 , 23 , 26 , 29 , 30 , 31 , 32 , 34 , 36 , 41 , 44 , 48 , 49 , 59 and propofol (4% increase, 6% decrease-14% increase, 9 arms) 16 , 17 , 30 , 41 , 52 , 54 , 60 , 61 , 63 ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 87%
“…However, data in this trial showed that the anti-shivering effect Tramadol was enhanced by Dexmetedomidine. Data in this trial showed a significantly lower ANS in the patient who treated with Dexmetedomidine, which implied that the advantage of Dexmedetomidine preoperative administering [18,19]. Intraoperative shivering in the cesarean section under spinal anesthesia is one of the most frequent surgical procedures in current clinical practices [9,20,21].…”
Section: Discussionmentioning
confidence: 96%
“…14 In addition, relatively invasive oral surgery can be performed safely in conscious sedation. 15 We considered that these cases should be managed under conscious sedation with sufficient analgesia although oral surgeons requested general anesthesia management in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…During conscious sedation, the reduction or abolition of physiological and psychological responses of the patient to surgery are obtained without a loss of consciousness, collaboration, and protective reflexes 14. In addition, relatively invasive oral surgery can be performed safely in conscious sedation 15. We considered that these cases should be managed under conscious sedation with sufficient analgesia although oral surgeons requested general anesthesia management in both cases.…”
Section: Discussionmentioning
confidence: 99%